2023
DOI: 10.1007/s10549-023-07016-9
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of high-grade breast ductal carcinoma in situ (DCIS): incidence and potential clinical impact

Abstract: Objective The purpose of this study was to investigate and classify the molecular subtypes of high-grade ductal carcinoma in situ (DCIS) and identify possible high-risk subtypes. The heterogenicity of DCIS with variable clinical and histopathological presentations has been recognized. Nevertheless, only histopathological grading and diameter are currently implemented in clinical decision-making following the diagnosis of DCIS. The molecular subtypes of DCIS and their IHC surrogate markers have no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…( 42 ) reported a significant difference between age and ER/PR expression, although they did not identify any significant variation between age and HER2 overexpression. In our earlier study, we identified that HER2 overexpression in cases classified as the HER2-enriched subtype was concurrent with early morphological invasive growth in high-grade DCIS ( 15 ). HER2 gene amplification in IBC is an independent poor prognostic factor ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…( 42 ) reported a significant difference between age and ER/PR expression, although they did not identify any significant variation between age and HER2 overexpression. In our earlier study, we identified that HER2 overexpression in cases classified as the HER2-enriched subtype was concurrent with early morphological invasive growth in high-grade DCIS ( 15 ). HER2 gene amplification in IBC is an independent poor prognostic factor ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Collected between 1996 and 2018, these samples represented 494 female patients diagnosed with DCIS of the breast. Experienced breast pathologists actively graded the histopathological specimens using the Van Nuys classification system ( 15 , 16 ). To our knowledge, this is the largest DCIS biobank that has been approved for cancer research purposes in Europe.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations